Let's go through the solving process step-by-step and fill in the missing terms and descriptions.
-
Start with the original equation: \[ 20(-4w - 4) = 11w + 11 \]
-
Apply the distributive property: \[ 20(-4w) + 20(-4) = 11w + 11 \] This simplifies to: \[ -80w - 80 = 11w + 11 \]
-
Now we have: \[ -80w - 80 = 11w + 11 \] Next, we will add 80 to both sides: \[ -80w = 11w + 11 + 80 \] This simplifies to: \[ -80w = 11w + 91 \]
-
Now, subtract \(11w\) from both sides: \[ -80w - 11w = 91 \] This simplifies to: \[ -91w = 91 \]
-
Now we will divide both sides by \(-91\): \[ w = \frac{91}{-91} \]
-
Finally, simplify the fraction: \[ w = -1 \]
Here is the complete process with all missing terms filled in:
- Start with the equation: \(20(-4w - 4) = 11w + 11\)
- Apply the distributive property: \(-80w - 80 = 11w + 11\)
- Add 80 to both sides: \(-80w = 11w + 91\)
- Subtract \(11w\) from both sides: \(-91w = 91\)
- Divide both sides by \(-91\): \(w = -1\)
Final answer: \[ w = -1 \]